2013
DOI: 10.1126/scisignal.2004712
|View full text |Cite
|
Sign up to set email alerts
|

Protein Interaction Network of the Mammalian Hippo Pathway Reveals Mechanisms of Kinase-Phosphatase Interactions

Abstract: The Hippo pathway regulates organ size and tissue homeostasis in response to multiple stimuli, including cell density and mechanotransduction. Pharmacological inhibition of phosphatases can also stimulate Hippo signaling in cell culture. We defined the Hippo protein-protein interaction network with and without inhibition of serine and threonine phosphatases by okadaic acid. We identified 749 protein interactions, including 599 previously unrecognized interactions, and demonstrated that several interactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

30
431
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(475 citation statements)
references
References 76 publications
30
431
1
5
Order By: Relevance
“…PP6 also suppresses IL-1-stimulated TAK1 activation by dephosphorylating TAK1 in 293 cells (15). Recent evidence suggests that PP6 may also regulate Hippo signaling via interaction with MOB1B (16). However, the physiological functions of PP6, especially in T cell biology, are not known.…”
mentioning
confidence: 96%
“…PP6 also suppresses IL-1-stimulated TAK1 activation by dephosphorylating TAK1 in 293 cells (15). Recent evidence suggests that PP6 may also regulate Hippo signaling via interaction with MOB1B (16). However, the physiological functions of PP6, especially in T cell biology, are not known.…”
mentioning
confidence: 96%
“…BioID has been used successfully to screen for constituents of the relatively insoluble mammalian nuclear lamina (1), the trypanosome bilobe (2), cell junction complexes (3)(4)(5), and centrosomes (6,7). The method also has been used to screen for proteins involved in the Hippo signaling pathway (8).…”
mentioning
confidence: 99%
“…They then tested the function of these proteins by RNAi knock-down and found that 102 of them affected the transcriptional activity of Yorkie. The two other studies by Wang et al [6] and Couzens et al, [7] from the groups of Junjie Chen and Anne-Claude Gingras, characterized the protein-protein interaction network of the human Hippo pathway and identified high-confidence networks of 343 and 445 proteins, respectively. All three studies rediscovered many of the known interactions between pathway components.…”
mentioning
confidence: 99%
“…Couzens et al [7] addressed how phosphorylation affects the Hippo pathway interaction network. They found that phosphorylation triggered remodeling of the interactomes of MST, LATS, and the MOB cofactors for LATS.…”
mentioning
confidence: 99%
See 1 more Smart Citation